Pengaruh Medical Collagen Sponge Dressing Terhadap Penyembuhan Luka Pasien Diabetes Melitus di Klinik Perawatan Luka Griya Walima Kota Lubuklinggau - Sidik, Nurlian; Z, Zulkarnain; Podesta, Ardiana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
A complication of diabetes mellitus sufferers is diabetic ulcers. Medical Collagen Sponge is a modern wound dressing in treating diabetic ulcers to accelerate tissue growth. The research problem is to overcome the problem of healing diabetic ulcer wounds in diabetes mellitus sufferers. The purposes of the research was to determine the effect of medical collagen sponge dressing on wound healing in diabetes mellitus patients at the Griya Walima Wound Care Clinic, Lubuklinggau City.This research uses quantitative research with a pre-experiment type of research approach, pre test-post test one group design by giving each respondent medical collagen sponge dressing treatment. The sampling technique was purposive sampling of 15 respondents.The results of the univariate analysis in this study showed that the average wound healing before the Medical Collagen Sponge Dressing intervention was 54.27%, while the average wound healing after the intervention was 17.7%. The results of the bivariate analysis have a p value of 0.000 < 0.005, meaning that there is an influence of medical collagen sponge dressing on wound healing in diabetes mellitus patients at the Griya Walima Wound Care Clinic, Lubuklinggau City. Educational institutions are expected to become a reference for the development of medical-surgical nursing knowledge in modern wound care. The Griya Walima Wound Care Clinic is expected to provide education for diabetes mellitus sufferers that treating diabetic ulcers using medical collagen sponge dressing accelerates wound healing.